Penerapan Pelayanan Prima Pada Layanan Wisata Pustaka Di Dinas Perpustakaan dan Kearsipan Kabupaten Sidoarjo - Dhea Hilda Maharani; Susi Hardjati (Public Inspiration : Jurnal Administrasi Publik, 2025)
The implementation of regional government is directed to accelerate the achievement of community welfare by improving services. The Sidoarjo Regency Library and Archives Office as a public service institution responsible for providing services to the community has provided excellent services that focus on the needs of the community. The library tour service program is one of the excellent services provided by the staff to the staff. This research aims to describe the application of excellent service in the Office in the Library Tourism Service program. With a qualitative descriptive method, the author analyzes six elements of excellent service: attitude, attention, action, ability, appearance, and responsibility. The research results show that the Sidoarjo Regency Library and Archives Office has implemented six elements of excellent service in this program.